KM Trajectory Schema Service Frame Work for Software Development Organizations - A. Krishna Priya, M; Selwyn, Justus (International Journal of Engineering and Technology, 2018)
Software Development Organizations are in the need to follow an effective KM strategy for Knowledge acquisition and Knowledge utilization. Even though, knowledge is available in the forms of documents, it is time consuming for the developers to identify and utilize the knowledge according to their need. Hence, we present a KM Trajectory Schema - Service Frame work which offers services for systematic Knowledge acquisition and Knowledge utilization.Â Knowledge is acquired from the development activity, and then the developerâ€™s code is stored in knowledge base. Knowledge Base Administrator designs a repository; knowledge base is appended by knowledge workers. Assessment and Evaluation of this Knowledge base is been done through the subject experts or knowledge champions. Finally Solution Knowledge Base is built and managed by Knowledge Base Administrators. KM service Framework facilitates Knowledge utilization by providing proactive semantic help for the software developers by the time of the development. KM Service Framework is an experimental collaborative platform that provides great service to the Software Development Organizations.Â